Auto-Industrial Development Recommendations for Uzbekistan: Lessons from the Experiences of the South Korea and Other Selected Countries - Uralov, Akhtamovich Shavkat (Graduate School of International Studies Ajou University, 2013)
This paper attempts to examine the experiences of the development of automobile industries in the Republic of Korea and other selected countries like China, India, Indonesia, Malaysia, and Brazil. Some of these countries succeeded in the development of automobile industry but some of them failed to develop mostly the national automobile industry. At the early stage of the development of automobile industry most of these countries used similar policies and protected their infant industries from foreign competitors but their achievements were different. This study investigates how Korea achieved to develop national automobile industry while some countries like Malaysia and Indonesia failed. The automobile industry is very capital and R&D intensive industry with high entry barriers and demanding rapid development. In this regard, in some cases except in countries with potential markets it is better to develop MNC-driven automobile industry like Brazil instead of national automobile industry with national brands. Based on experiences of selected countries this paper concludes that Uzbekistan made right decision to develop automobile industry in form of joint venture with MNC and has not attempted to develop national automobile industry with national brands.
학위논문(석사)아주대학교 국제대학원 :국제통상학과,2013. 8